Synthesis of new fluorescent molecules having an aggregation-induced emission property derived from 4-fluoroisoxazoles - Sato, Kazuyuki; Kawasaki, Akira; Karuo, Yukiko; Tarui, Atsushi; Kawai, Kentaro; Omote, Masaaki (Beilstein Journal of Organic Chemistry, 2020)
Fluorescent molecules based on a fluorinated isoxazole scaffold were synthesized and investigated for their photochemical properties. The introduction of a fluorine substituent into 3,5-diarylisoxazoles led to an increase of fluorescence intensity and exhibited a redshift in the emission intensity. α-Fluorinated boron ketoiminates (F-BKIs) were also synthesized via a ring-opening reaction of 4-fluoroisoxazoles and exhibited highly fluorescent luminescence and aggregation-induced emission (AIE), showing promise as a new fluorophore.
Keywords: aggregation-induced emission; boron ketoiminates; fluorescent probe; α-fluorinated boron ketoiminates; 4-fluoroisoxazoles

(untitled) - Carter, K. P.; Young, A. M.; Palmer, A. E. (Chem. Rev., 2014)

(untitled) - Guo, Z.; Park, S.; Yoon, J.; Shin, I. (Chem. Soc. Rev., 2014)

(untitled) - Niu, L.-Y.; Chen, Y.-Z.; Zheng, H.-R.; Wu, L.-Z.; Tung, C.-H.; Yang, Q.-Z. (Chem. Soc. Rev., 2015)

(untitled) - Liu, H.-W.; Chen, L.; Xu, C.; Li, Z.; Zhang, H.; Zhang, X.-B.; Tan, W. (Chem. Soc. Rev., 2018)

(untitled) - Li, H.; Vaughan, J. C. (Chem. Rev., 2018)

(untitled) - Gao, P.; Pan, W.; Li, N.; Tang, B. (Chem. Sci., 2019)

(untitled) - Wang, L.; Frei, M. S.; Salim, A.; Johnsson, K. (J. Am. Chem. Soc., 2019)

(untitled) - Jenekhe, S. A.; Osaheni, J. A. (Science, 1994)

(untitled) - Qian, J.; Tang, B. Z. (Chem, 2017)

(untitled) - Gu, X.; Kwok, R. T. K.; Lam, J. W. Y.; Tang, B. Z. (Biomaterials, 2017)

(untitled) - Mei, J.; Huang, Y.; Tian, H. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Wang, D.; Tang, B. Z. (Acc. Chem. Res., 2019)

(untitled) - Gao, M.; Tang, B. Z. (Coord. Chem. Rev., 2020)

(untitled) - Niu, G.; Zhang, R.; Shi, X.; Park, H.; Xie, S.; Kwok, R. T. K.; Lam, J. W. Y.; Tang, B. Z. (TrAC, Trends Anal. Chem., 2020)

(untitled) - Kuduk, S. D.; DiPardo, R. M.; Bock, M. G. (Org. Lett., 2005)

(untitled) - Shestopalov, A. M.; Rodinovskaya, L. A.; Fedorov, A. E.; Kalugin, V. E.; Nikishin, K. G.; Shestopalov, A. A.; Gakh, A. A. (J. Fluorine Chem., 2009)

(untitled) - Dubbaka, S. R.; Narreddula, V. R.; Gadde, S.; Mathew, T. (Tetrahedron, 2014)

(untitled) - Allen, L. J.; Muhuhi, J. M.; Bland, D. C.; Merzel, R.; Sanford, M. S. (J. Org. Chem., 2014)

(untitled) - Xiong, H.; Hoye, A. T.; Fan, K.-H.; Li, X.; Clemens, J.; Horchler, C. L.; Lim, N. C.; Attardo, G. (Org. Lett., 2015)

(untitled) - Katoh, T.; Tomata, Y.; Tsukamoto, T.; Nakada, Y. (Tetrahedron Lett., 2015)

(untitled) - Lee, H. G.; Milner, P. J.; Buchwald, S. L. (J. Am. Chem. Soc., 2014)

(untitled) - Fier, P. S.; Hartwig, J. F. (J. Am. Chem. Soc., 2014)

(untitled) - Wang, C.; Cai, J.; Zhang, M.; Zhao, X. (J. Org. Chem., 2017)

(untitled) - Harsanyi, A.; Conte, A.; Pichon, L.; Rabion, A.; Grenier, S.; Sandford, G. (Org. Process Res. Dev., 2017)

(untitled) - Marque, S.; Snoussi, H.; Loupy, A.; Plé, N.; Turck, A. (J. Fluorine Chem., 2004)

(untitled) - Ryan, S. J.; Schimler, S. D.; Bland, D. C.; Sanford, M. S. (Org. Lett., 2015)

(untitled) - Schimler, S. D.; Ryan, S. J.; Bland, D. C.; Anderson, J. E.; Sanford, M. S. (J. Org. Chem., 2015)

(untitled) - Sloop, J. C.; Jackson, J. L.; Schmidt, R. D. (Heteroat. Chem., 2009)

(untitled) - Qian, J.; Liu, Y.; Zhu, J.; Jiang, B.; Xu, Z. (Org. Lett., 2011)

(untitled) - Stephens, C. E.; Blake, J. A. (J. Fluorine Chem., 2004)

(untitled) - Campbell, T. F.; Stephens, C. E. (J. Fluorine Chem., 2006)

(untitled) - Hatfield, J. M.; Eidell, C. K.; Stephens, C. E. (Tetrahedron Lett., 2013)

(untitled) - Sato, K.; Sandford, G.; Shimizu, K.; Akiyama, S.; Lancashire, M. J.; Yufit, D. S.; Tarui, A.; Omote, M.; Kumadaki, I.; Harusawa, S.; Ando, A. (Tetrahedron, 2016)

(untitled) - Macedo, F. P.; Gwengo, C.; Lindeman, S. V.; Smith, M. D.; Gardinier, J. R. (Eur. J. Inorg. Chem., 2008)

(untitled) - Koyama, Y.; Matsumura, T.; Yui, T.; Ishitani, O.; Takata, T. (Org. Lett., 2013)

(untitled) - Yoshii, R.; Nagai, A.; Tanaka, K.; Chujo, Y. (Chem. – Eur. J., 2013)

(untitled) - Minuti, L. F.; Memeo, M. G.; Crespi, S.; Quadrelli, P. (Eur. J. Org. Chem., 2016)

(untitled) - Dohe, J.; Koßmann, J.; Müller, T. J. J. (Dyes Pigm., 2018)

(untitled) - Yamada, S.; Morita, M.; Konno, T. (J. Fluorine Chem., 2017)